Ileal lymphangioma as a cause of intestinal obstruction in an adult patient: A rare case report - Vora, Hasmukh Babaldas; Sharma, Badri Narayan (Indian Journal of Case Reports, 2025)
Most abdominal lymphangiomas are diagnosed at a very early age and are rarely found in adults. Abdominal lymphangioma is mainly found in the visceral organs, the retroperitoneum, the mesentery, or in the bones. In the gastrointestinal tract, they comprise